Insomnia symptoms and the risk of all-cause mortality among stroke survivors - Sawadogo, Wendemi; Adera, Tilahun; Alattar, Maha; Perera, Robert; Burch, James (BMC Public Health, 2024)
Insomnia is more frequently reported in stroke survivors but its independent role in mortality in stroke survivors is unknown. The purpose of this study was to investigate the association of insomnia symptoms with all-cause mortality among stroke survivors.
Keywords: Age difference; All-cause mortality; Insomnia symptoms; Sex difference; Stroke survivors; dept.phc; peer-reviewed